2000
DOI: 10.1051/rnd:2000131
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a mixed-management system on the release of oxytocin, prolactin, and cortisol in ewes during suckling and machine milking

Abstract: -Milk yield and plasma oxytocin (OT), prolactin (PRL), and cortisol (CORT) during suckling and machine milking were measured in multiparous ewes subjected to a mixed management system of 3 sucklings and two daily milkings. Peak hormones were significantly increased and were similar during suckling and milking for PRL (181 vs. 163.3 ng·mL -1 ) and CORT (12.5 vs. 11.5 ng·mL -1 ). During the period of exclusive suckling, OT was always significantly released (90.3 pg . mL -1 ); however, during the period of mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
3
19

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 25 publications
5
38
3
19
Order By: Relevance
“…A similar kind of CORT profile has been reported following stress imposed by weaning. However, CORT levels generally return to normal values three or four days after weaning [7,8]. This type of adaptation was not observed in the present study because CORT levels of the Gir group remained high in response to milking throughout the experiment.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…A similar kind of CORT profile has been reported following stress imposed by weaning. However, CORT levels generally return to normal values three or four days after weaning [7,8]. This type of adaptation was not observed in the present study because CORT levels of the Gir group remained high in response to milking throughout the experiment.…”
Section: Discussioncontrasting
confidence: 59%
“…Moreover, some authors have reported that stress caused by first milkings following parturition or weaning is always accompanied by a lack of OT release and disturbed milk ejection [6][7][8], which was not recorded here.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations